Effective bandpass filtering for spoof surface plasmon polariton transmission lines. (3rd April 2019) - Liao, Shaowei; Qi, Chu; Xue, Quan
Abstract: Effective spoof surface plasmon polariton (SSPP) bandpass filtering with a simple structure based only on SSPP transmission lines (TLs) is proposed, which has a different working principle from previous versions. SSPP sections are placed beside a main SSPP TL, introducing resonances leading to transmission zeros to the main SSPP TL. By utilizing the SSPP TL sections' strong dispersion characteristics to merge transmission zeros, a continuous stopband is obtained ensuring good out-of-band rejection and selectivity at the lower band. A domino SSPP working in the microwave band is adopted to demonstrate the idea. A prototype is designed and fabricated to confirm the validity of the proposed method.